Electrochemical Preparation of Hydroxylated Boron Nitride Nanosheets for Solid-State Flexible Supercapacitors Using Deep Eutectic Solvent and Water Mixture as Electrolytes - Shan, Qian (Langmuir : the ACS journal of surfaces and colloids, 2022)
One-step and efficient preparation of few-layer hydroxylated boron nitride nanosheets (OH-BNNSs) in electrochemical methods is still challenging. Here, we developed an electrolyte composed of a mixture of deep eutectic solvent (DES, choline chloride-urea) and water for electrochemical methods to enhance the exfoliation and oxidation processes, enabling the one-step preparation of OH-BNNSs. It was found that the obtained OH-BNNSs were an average lateral size of 625 nm and thickness of six layers. Furthermore, the OH-BNNSs and DES were added to the poly(vinyl alcohol) (PVA) substrate to prepare composite gel polymer electrolyte (PVA/DES/OH-BNNSs GPE) for solid-state flexible supercapacitor. The OH-BNNSs can effectively shorten the ionic transport distance and enhance ion conductivity. In addition, their excellent mechanical properties can significantly prevent the electrolyte structure from collapsing during reuse. In the meantime, DES was introduced to improve ionic conductivity and broaden the operating voltage window of supercapacitor. As a result, the symmetric solid-state flexible supercapacitor consisting of activated carbon electrodes and PVA/DES/OH-BNNSs GPE appeared a wide voltage window of 2.3 V, high specific capacitance of 151.22 F g-1 at 0.1 A g-1 and remained 98% capacitance after 1500 charge-discharge cycles. This study not only opened a new pathway to efficient exfoliation of insulating layered materials but also found a novel gel polymer electrolyte for solid-state flexible supercapacitors